IN-VITRO AND IN-VIVO EVALUATION OF Adansonia digitata AND Azadirachta indica WOOD ASH AS NATURAL REPELLENTS AND ACARICIDES AGAINST LICE INFESTATION IN POULTRY FARMS IN KADUNA - Yayock, Hosea Chigari; Kadani, Esther Godiya; Basira, Ibrahim; Auta, Kato Ishaya (FUDMA Journal of Sciences, 2026)
Poultry production supports food security and economic growth, yet infestations by wing lice (Lipeurus caponis) and chicken body louse (Menacanthus stramineus) threaten productivity. Synthetic insecticides/acaricides raise safety concerns, prompting the search for eco-friendly alternatives. The study evaluated the acaricidal (insecticidal) and repellency efficacy of wood ash from Adansonia digitata (baobab) and Azadirachta indica (neem) against poultry lice collected in a selected poultry farm located in Kaduna metropolis, Kaduna state Nigeria. The selected stem-barks of the trees were collected, authenticated, vouchered and processed to wood-ash at the Department of Biological Sciences, Kaduna State University; Geochemical analysis assessed metal content and pH (9.01–10.75). In-vitro repellency and kill-time assays (0.25–1.0 g/cm³) used 20–25 lice per trial, while in-vivo assays and hematological evaluations (50–150 g/kg) determined physiological effects. A. digitata (baobab) showed higher repellency (84.4% at 0.25 g/cm2) and faster mortality (40 min at 1.0 g/cm³) than A. indica. Acaricidal / Insecticidal bioassay reveals A. digitata (1.0 g/cm²) achieved 93.3% mortality by 48 hours, while A. indica. (neem) reached 78.3%. Wood ashes, particularly from A. digitata, offer eco-safe, effective alternatives for sustainable poultry lice management.